CORRUPT DATA ON MRI WORKSTATION - Ailifia Dian Rizqi Arshyva (Poltekkes Kemenkes Semarang, 2024)
During the internship at the Radiology Installation at Ken Saras Hospital in Semarang Regency, the MRI examination service was well organized, with a structured work flow, including scheduling, patient education, carrying out examinations, and communicating results via WhatsApp messages. However, there are challenges that must be faced by the Radiology Installation at Ken Saras Hospital, especially in technical terms. Even though the MRI equipment is 12 years old, it may present a risk of hardware failure resulting in errors on the MRI workstation. One recurring problem is the appearance of corrupt data in MRI scanning images. The main objective of this community service is to improve the technical skills of radiographers in overcoming and preventing data corruption problems at MRI workstations. Intensive training will be provided to enrich their understanding of MRI technology, identify causes of data corruption, and implement necessary technical solutions